Tempeh flour as an excellent source of paraprobiotics - WILFADRI PUTRA JONESTI; CAHYA PRIHATNA; GRISELDA HERMAN NATADIPUTRI; ANTONIUS SUWANTO; ANJA MERYANDINI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Jonesti WP, Prihatna C, Natadiputri GH, Suwanto A, Meryandini A. 2023. Tempeh flour as an excellent source of paraprobiotics. Biodiversitas 24: 1817-1823. Tempeh, a functional fermented food from Indonesia, has many benefits for human health. The presence of oligosaccharides, live and dead microbes in tempeh can function as prebiotics, probiotics, or paraprobiotics. This study aimed to determine the composition of live and dead lactic acid bacteria (LAB) and Enterobacteriaceae in tempeh flour using microbiological and molecular quantifications. Two samples of tempeh flour based on the drying process, i.e., sun-dried and oven-dried, were analyzed. Bacteria were quantified using standard plate count and qPCR, while bacterial cells damaged by the drying process were quantified using Propidium Monoazide-Quantitative Polymerase Chain Reaction (PMA-qPCR). Tempeh flours contained live bacteria as many as 4-5 log CFU/g and intact dead bacterial cells as many as 9 log CFU/g. The number of bacteria only differed slightly between the two drying processes. Based on qPCR analysis, the LAB number was higher than Enterobacteriaceae in tempeh flour. In addition, the bacterial population by qPCR was higher than by cultured analysis. These results indicated that sun-dried or oven-dried tempeh flour could be a functional food because it contained high amounts of live and dead bacteria as candidates for probiotics and paraprobiotics based on PMA-qPCR analysis.